Democratic localism and the implementation of the Community Remedy in England and Wales - Heap, Vicky (Criminology & criminal justice, 2021)
This article assesses the development and implementation of the Community Remedy anti-social behaviour policy by Police and Crime Commissioners (PCCs) in England and Wales. The Community Remedy, introduced by the Anti-Social Behaviour, Crime and Policing Act (2014), allows victims of ‘low-level’ anti-social behaviour to select an informal action for their offender from a list designed by their local PCC via consultation with the public. This article reports the results of a benchmarking exercise that investigates how PCCs have translated this policy into practice by examining: public consultation procedures; the contents of the Community Remedy documents; and police usage. The findings indicate an uneven implementation across regions with variable levels of engagement from PCCs, police forces and members of the public. We assess the enactment and adoption of this new power alongside its potential to stimulate democratic localism.